2013
DOI: 10.1063/1.4800782
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral distributions of pseudo-turbulent bubbly flows

Abstract: An experimental study was carried out to determinate the power spectral density (PSD) of mono-dispersed bubbly flows in a vertical channel using flying hot-film anemometry. To improve bubble detection, optical fibers were installed in close proximity to the anemometer sensing element; in this way, the collisions of bubbles with the probe can be detected and removed from the signal. Measurements were performed with gas fractions up to 6%. The PSD distributions were found to decay with a power of −3, in agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 26 publications
(22 reference statements)
9
38
0
Order By: Relevance
“…In their work bubble-bubble interaction was investigated and the influence of the bubbles on the fluid energy spectra was addressed. A slope of -3.2 of the double-logarithmic energy spectrum of the velocity fluctuation was observed which is in close agreement with (Mendez-Diaz et al, 2013) for a similar configuration. In a previous work Mendez- Diaz et al (2012) collected several experimental results to develop a criterion of void fraction distribution as a function of the bubble Reynolds number and of Weber number.…”
Section: Introductionsupporting
confidence: 87%
“…In their work bubble-bubble interaction was investigated and the influence of the bubbles on the fluid energy spectra was addressed. A slope of -3.2 of the double-logarithmic energy spectrum of the velocity fluctuation was observed which is in close agreement with (Mendez-Diaz et al, 2013) for a similar configuration. In a previous work Mendez- Diaz et al (2012) collected several experimental results to develop a criterion of void fraction distribution as a function of the bubble Reynolds number and of Weber number.…”
Section: Introductionsupporting
confidence: 87%
“…Here, the drag coefficient of a sphere moving at constant velocity in a fluid at rest is estimated by using the correlation of Schiller Riboux et al (2010). Nevertheless, the experimental investigation of a bubble swarm by Mendez-Diaz et al (2013) has not confirmed the validity of the scaling in d/C d for a larger range of Reynolds numbers (70 Re 1000). In the absence of a reliable law for Λ, it cannot be concluded whether the integral length scale measured in the array of spheres is determined by the same mechanism as that of a real bubble swarm or not.…”
Section: Wavenumber Spectra Of Velocity Fluctuationsmentioning
confidence: 99%
“…It is also not proportional to the diameter of bubble, but rather corresponds to the length of the bubble wake (Risso et al 2008). There is, however, no consensus on its exact expression (Mendez-Diaz et al 2013). These two first quantities characterize the large energetic scales of the agitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning liquid dynamics, it is now well established that bubble-induced agitation has features that make it different from shear-induced turbulence. A series of experimental investigations carried out in homogeneous columns have led to a rather complete description of its properties (Martínez-Mercado, Palacios-Morales & Zenit 2007;Martínez-Mercado et al 2010;Riboux, Risso & Legendre 2010;Mendez-Diaz, Serrano-García & Zenit 2013). On the other hand, no fundamental investigation of bubble-induced mixing has been performed so far, except for the preliminary work of Mareuge & Lance (1995), which was limited to a single very small value of the gas volume fraction, α = 0.2 %.…”
mentioning
confidence: 97%